Conditions of resonance interaction of acoustic periodic waves interaction - Lavcel-Budko, Olga; Krylovas, Aleksandras (Lietuvos matematikos rinkinys, 2014)
We consider differential equations of gas dynamics, when the thermal conductivity and viscosity coefficients equal zero. The system is supplemented with equations of state for the gas pressure and the total energy; these equations do not depend on the properties of gas, i.e. are of a general form. We construct asymptotical approximation for the resonance interaction of acoustic periodic waves, which is uniformly valid in the long time interval. A system coefficient allows determining the resonance occurring condition the relation between gas pressure and temperature at the initial time. We investigate the ideal and non-ideal gas and determine the relationship between the parameters, which causes the of resonanse vanishing in non-ideal gas.
Keywords: gas dynamics; acoustic waves; resonance; asymptotics methods